Factors associated with running injuries - Jennings, K.
1.0 Introduction 2.0 Incidence of Running Injuries 3.0 Classification of Running Injuries in the Lower Limb 4.0 Factors Associated with the Incidence of Lower Extremity Running Injuries 4.1 Running Distance/Running Frequency 4.2 Training Speed 4.3 Warm-up, Stretching Exercises and Cool-down 4.4 Running Surfaces 4.5 Footwear 4.6 Age 4.7 Running Experience 4.8 Previous Injury 5.0 Influence of Running Biomechanics on Running Injury 5.1 Anthropometrics 5.2 Limb Morphology 5.3 Learned/Developed Movement Patterns 6.0 Conclusion In conclusion, individuals who participate in the sport of running put themselves at a high risk of incurring a wide variety of injuries. It was the purpose of this review to document the incidence and type of these running related injuries and to evaluate the risk factors associated with these lower extremity injuries. The most common podiatric injuries sustained by runners include stress fractures, shin splints and shearing and stress problems such as blisters and callous. A strong, positive correlation of the incidence of running injuries has been identified with weekly running distance and previous injury and a negative association between running injuries and previous running experience (Marti, 1991; Macera, 1992; Hoebrigs, 1992 and Van Mechelen, 1992). These authors also consistently reported that age, gender and running on hard surfaces are not significant risk factors for running injuries. Brill and Macera (1995) and Macera (1992) conclude that warm-up, stretching exercises and cool-down as potential risk factors also require further investigation. When overuse injuries of the lower limbs are diagnosed in athletes, the structure and function of the foot should be examined. The biomechanical and clinical skills of the podiatrist are valuable in the sport of running and gives the podiatrist the opportunity to practice podiatric sports medicine within the context of a sports medicine team.